Timing synchronization algorithm based on clock skew estimation for WSN - Yi SUN; Lu-kun ZENG; Xin WU; Jun LU; Yue SUN (Tongxin xuebao)
In order to solve the problem of poor synchronization stability on classical synchronization algorithm,high overhead on joint clock offset and skew correction synchronization algorithm in wireless sensor network,a timing syn-chronization algorithm based on clock skew estimation for WSN (CSMS) was proposed.The algorithm adopted low-overhead clock offset and skew estimation method to improve the synchronization precision and stability of paired node.At the same time of guaranteeing the stability and accuracy,it realized synchronization with the root node and the neighbors,and optimized synchronization overhead by using the combination of hierarchical network structure and radio listening.The experimental results show that the CSMS algorithm balances energy consumption,accuracy and stability of synchronization.